Assessing bone formation on hydrophilic and hydrophobic implant surfaces in a murine model treated with bisphosphonates - Sánchez-Puetate, Julio Cesar [UNESP]; Silva, Bruno Luís Graciliano [UNESP]; Pinotti, Felipe Eduardo [UNESP]; Marcantonio, Camila Chierici [UNESP]; de Oliveira, Guilherme José Pimentel Lopes; Junior, Elcio Marcantonio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (Springer Nature, 2024)
Objective: To evaluate the osseointegration of implants with hydrophobic (HFB) and hydrophilic (HFL) surfaces in a murine model of high-dose bisphosphonates (BPs). Materials and methods: Sixty-four rats were randomly allocated into four groups: control group with HFB implants (CG-HFB), control group with HFL implants (CG-HFL), BP group with HFB implants (BP-HFB), and BP group with HFL implants (BP-HFL). Animals were euthanized after 15 and 45 days (n=8). The dependent variables assessed were the removal torque (biomechanical analysis), the bone volume around the implants (%BV/TV) (microtomographic analysis), the bone-implant contact (%BIC), the bone between the threads (%BBT) (histomorphometric analysis), and the expression of bone metabolism markers (immunohistochemistry analysis). Results: The CG-HFL and BP-HFL groups presented higher removal torque than the CG-HFB and BP-HFB implants. The %BIC of the CG-HFL surfaces was slightly higher than that of the CG-HFB implants. The BP-HFB and BP-HFL groups presented a higher %BIC than that of the CG-HFB and CG-HFL groups (p<0.001). BP therapy also increased the %BBT at both implant surfaces. Higher levels of ALP were observed in the matrix region of bone tissue on the HFL surfaces than on the HFB surfaces. Conclusion: Both surfaces enable osseointegration in rats under BP therapy. Clinical relevance: The study demonstrates that hydrophobic (HFB) and hydrophilic (HFL) implant surfaces can promote osseointegration in rats undergoing bisphosphonate therapy. The HFL surfaces exhibited improved biomechanical performance, higher bone-implant contact, and increased bone volume, suggesting their potential clinical relevance for implant success in individuals on bisphosphonate treatment.
Keywords: Bisphosphonates; Dental implants; Osseointegration; Surface properties